THE APPLICATION OF CONSISTENCY OF TREATMENT IN DISMISSALS FOR MISCONDUCT - Brenda Grant; Asheelia Behari (Obiter, 2021)
Fairness in employment necessitates that the employer apply consistent disciplinary standards in the workplace, so that employees who commit the same or similar disciplinary infraction are treated equally. The Code of Good Practice: Dismissal (in Schedule 8 of the Labour Relations Act 55 of 1995) sets out a range of guidelines to be applied by the employer before a decision to dismiss an employer may be taken. It seeks to protect employees from arbitrary action by the employer in order to achieve a measure of employment justice. Employers must therefore apply the rules of the workplace consistently by effecting discipline against all employees accountable for similar misconduct, and also by applying the same sanction for similar infractions. The principle of consistent treatment of employees is referred to as the “parity principle”. It provides that employees who participate in the same or similar wrongdoing, with no distinguishing factors from one case to another, should be penalized in the same way. The foundation of the principle lies in the notion that similar cases must be treated in a similar fashion. It is based on the principle of reasonableness in that fairness in the workplace requires the application of reasonable rules, and not arbitrary or irrational opinions of the employer. Reasonable rules will reflect generality and equality and invariably lead to legal certainty, and a failure by the employer to apply those standards consistently may lead to a finding that the employer acted unfairly in dismissal disputes. In addition to the requirement of consistency, an employer is required to consider a range of other factors before taking the decision to dismiss an employee. These include the gravity of the misconduct; the nature of the work performed by the employee; the circumstances under which the infraction occurred; and the employee’s personal circumstances which may relate to the previous disciplinary record of the employee; his/her length of service and the employee’s personal circumstances. The consideration of these circumstances often leads to a tension between applying the requirement of consistency on the one hand, and the need to take into account the specific circumstances of the employee and circumstances of the misconduct. This comment explores the different approaches adopted by the courts in determining whether or not inconsistent treatment by the employer justifies a finding that the dismissal of an employee was unfair in view of the obligation to take into account the other factors required in the Code. These issues often arise in circumstances where an employee is dismissed by an employer and claims that the employer acted unfairly because other employees were given less severe sanctions for the same or similar misconduct. In deciding the fairness of the matter, the courts have drawn a distinction between individual misconduct and collective misconduct. Historical inconsistency is generally applied in cases of individual misconduct, whilst contemporaneous inconsistency is applied in circumstances of collective misconduct.